2006
DOI: 10.1038/labinvest.3700368
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming liver-stem WB cells into functional insulin-producing cells by persistent expression of Pdx1- and Pdx1-VP16 mediated by lentiviral vectors

Abstract: Adenovirus-mediated transient expression of the pancreatic duodenal homeobox transcription factor Pdx1 in mouse liver activates pancreatic endocrine and exocrine genes, the latter reportedly resulting in severe hepatitis. Expression of a super-active form of Pdx1 or Pdx1-VP16 selectively transdifferentiates hepatic WB cells into functional pancreatic beta-like insulin-producing cells, without evidence of exocrine differentiation. No study has systematically compared the transdifferentiation efficiency of Pdx1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 29 publications
(57 reference statements)
1
55
0
Order By: Relevance
“…With these cell lines, we studied: the repertoire of both short-term and long-term expression of Pdx1-or Pdx1-VP16-induced pancreatic gene expression; and their capacity to serve as beta-cell surrogates in restoring euglycemia in streptozotocin-treated diabetic mice. We found that cell lines expressing either Pdx1 or Pdx1-VP16 long-term exhibited similar profiles for expression of genes related to pancreatic β-cell development and function; and similar capacity of reversal of hyperglycemia in diabetic mice [3]. However, short-term expression of Pdx1 or Pdx1-VP16 demonstrated that Pdx1-VP16 is much more efficient in initiating liver-to-pancreas transdifferentiation [3], this finding confirming the recent observations that adenovirus-mediated transient expression of Pdx1-VP16 in mouse liver is more effective than Pdx1 [22,23].…”
Section: Effectiveness Of Pdx1 Versus Pdx1-vp16 In Liver-to-pancreas mentioning
confidence: 78%
See 4 more Smart Citations
“…With these cell lines, we studied: the repertoire of both short-term and long-term expression of Pdx1-or Pdx1-VP16-induced pancreatic gene expression; and their capacity to serve as beta-cell surrogates in restoring euglycemia in streptozotocin-treated diabetic mice. We found that cell lines expressing either Pdx1 or Pdx1-VP16 long-term exhibited similar profiles for expression of genes related to pancreatic β-cell development and function; and similar capacity of reversal of hyperglycemia in diabetic mice [3]. However, short-term expression of Pdx1 or Pdx1-VP16 demonstrated that Pdx1-VP16 is much more efficient in initiating liver-to-pancreas transdifferentiation [3], this finding confirming the recent observations that adenovirus-mediated transient expression of Pdx1-VP16 in mouse liver is more effective than Pdx1 [22,23].…”
Section: Effectiveness Of Pdx1 Versus Pdx1-vp16 In Liver-to-pancreas mentioning
confidence: 78%
“…We found that cell lines expressing either Pdx1 or Pdx1-VP16 long-term exhibited similar profiles for expression of genes related to pancreatic β-cell development and function; and similar capacity of reversal of hyperglycemia in diabetic mice [3]. However, short-term expression of Pdx1 or Pdx1-VP16 demonstrated that Pdx1-VP16 is much more efficient in initiating liver-to-pancreas transdifferentiation [3], this finding confirming the recent observations that adenovirus-mediated transient expression of Pdx1-VP16 in mouse liver is more effective than Pdx1 [22,23]. In summary, long-term, persistent expression of either Pdx1 or Pdx1-VP16 is similarly effective in converting hepatic stem cells into pancreatic endocrine precursor cells that, upon transplantation into diabetic mice, can become functional IPCs and restore euglycemia.…”
Section: Effectiveness Of Pdx1 Versus Pdx1-vp16 In Liver-to-pancreas mentioning
confidence: 78%
See 3 more Smart Citations